2018
DOI: 10.1099/ijsem.0.002975
|View full text |Cite
|
Sign up to set email alerts
|

Flagellimonas aquimarina sp. nov., and transfer of Spongiibacterium flavum Yoon and Oh 2012 and S. pacificum Gao et al. 2015 to the genus Flagellimonas Bae et al. 2007 as Flagellimonas flava comb. nov. and F. pacifica comb. nov., respectively

Abstract: A Gram-stain-negative, non-spore-forming, rod-shaped, aerobic and diffusible yellow-coloured bacterial strain, designated strain ECD12 was isolated from a seaweed, Ecklonia cava. The isolate required sea salts for growth. Catalase-positive and oxidase-negative. A phylogenetic tree based on 16S rRNA gene sequences showed that strain ECD12 formed an evolutionary lineage within the radiation enclosing the members of genera Spongiibacterium and Flagellimonas sharing the highest similarity to Flagellimonas ecklonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In the light of these results, we propose to include Flagellimonas and Spongiibacterium in Muricauda , which has priority. This solution appears to be preferable compared to a recent proposal that only transferred Spongiibacterium to Flagellimonas (Choi et al, 2018). Additional supermatrix analyses indeed confirmed that Flagellimonas and Spongiibacterium are nested within Muricauda , whereas Croceitalea (Lee et al, 2008; Yoon and Oh, 2012; Su et al, 2017) and Croceivirga (Hu et al, 2017) form independent lineages (Supplementary Data Sheet 1).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the light of these results, we propose to include Flagellimonas and Spongiibacterium in Muricauda , which has priority. This solution appears to be preferable compared to a recent proposal that only transferred Spongiibacterium to Flagellimonas (Choi et al, 2018). Additional supermatrix analyses indeed confirmed that Flagellimonas and Spongiibacterium are nested within Muricauda , whereas Croceitalea (Lee et al, 2008; Yoon and Oh, 2012; Su et al, 2017) and Croceivirga (Hu et al, 2017) form independent lineages (Supplementary Data Sheet 1).…”
Section: Resultsmentioning
confidence: 89%
“…The description is as for Flagellimonas aquimarina (Choi et al, 2018). The type strain is ECD12 = KCTC 52351 = JCM 32292.…”
Section: Discussionmentioning
confidence: 99%
“…parva, small, pertaining to the small colonial morphology on agar medium). The description was given by Choi et al [17]and Gao et al [61].…”
Section: Description Of Muricauda Aurantiaca Nom Novmentioning
confidence: 99%
“…193 [5]. At the time of writing, Muricauda comprises 28 species, which were all isolated from marine environments, such as Muricauda lutaonensis from a coastal hot spring [6], four species from marine tidal flats [7][8][9][10], Muricauda aquimarina and Muricauda flavescens from a salt lake [2], Muricauda amoyensis from coast sand [11], eight species from sea water [3,[12][13][14][15][16], Muricauda koreensis from seaweed [17], five species from sea sediments [1,[18][19][20][21], Muricauda eckloniae from marine alga [22], Muricauda flava and Muricauda hymeniacidonis from marine sponges [23,24], Muricauda marina from marine snow [25], Muricauda amphidinii from dinoflagellate [26], and Muricauda alvinocaridis from shrimp gill [27]. M. eckloniae, M. flava and M. koreensis were described as Flagellimonas eckloniae, Spongiibacterium flavum and Flagellimonas aquimarina, respectively, but García merged Flagellimonas and Spongiibacterium into Muricauda and these three species were transferred to Muricauda.…”
Section: Introductionmentioning
confidence: 99%
“…The strain was routinely cultured on MA at 25 °C and stored as a suspension in skimmed milk (10 %, w/v) at −80 °C. Pseudozobellia thermophila KCTC 22016 T [17] and Flagellimonas flava KCTC 22665 T [18, 19] were obtained from their respective culture collection centres. These two strains were used as reference strains and routinely grown on MA at 25 °C.…”
Section: Isolation and Ecologymentioning
confidence: 99%